Enzymatic Synthesis of Biodegradable Polyesters using Succinic Acid Monomer Derived from Cellulose of Oil Palm Empty Fruit Bunch. (2nd November 2018) - Pasma, Satriani Aga; Daik, Rusli; Maskat, Mohamad Yusof
Abstract : Oil palm empty fruit bunch fiber (OPEFB) is a lignocellulosic waste from palm oil mills. It is a potential source of glucose and xylose that can be used as raw materials for the production of valuable compounds such as succinic acid. The present study aims at producing biodegradable polyesters from OPEFB-derived monomer using enzymatic polymerization. Cellulose was extracted from OPEFB by using organosolv method. Enzymatic hydrolysis of cellulose was carried out using Celluclast and Novozyme 188 at 40 °C, with agitation rate of 145 rpm. Amount of enzyme and cellulose as well as reaction time were varied. The highest glucose concentration produced was 167.4 g/L. Succinic acid was produced when glucose was subjected to fermentation using Actinobacillus succinogenes with the highest concentration of 23.50 g/L. Biodegradable polyesters were produced when succinic acid together with 1, 4-butanediol, glycerol and ethylene glycol, respectively, were subjected to Lipase ( Candida Antartica CALB). Molecular weight obtained for poly(butylene succinate), poly(glycerol succinate), and poly(ethylene succinate) were 5.90 × 10 4, 6.20 × 10 4, and 4.53 × 10 4 g/mol, respectively. The greatest extent of biodegradability of polyester found was 78.65 ± 0.65%.